Exploring Liquidity Risk and Interest-Rate Risk: Implications for Profitability and Firm Value in Nigerian Banks - Ebenezer, Olalere Oluwaseyi; Islam, Md. Aminul; Yusoff, Wan Sallha; Sobhani, Farid Ahammad (Journal of Reviews on Global Economics, 2018)
The purpose of this paper is to examine the effects of liquidity risk and interest rate risk on profitability and firm value, current studies are typically limited in emerging markets. This study employs a panel data estimation technique and a sample of 16 banks operating in Nigeria over the period from 2009 to 2017 making up to 144 observations. The findings of the study reveal that liquidity risk (loan to deposit ratio and liquid asset ratio) have a significant negative effect on firm value, the net interest margin and GDP have a negative significant impact on firm value for Nigerian banks. The loan to deposit ratio have a negative significant effect on firm value while the liquid asset ratio have a positive effect on firm value. The net interest margin have a negative significant effect on firm value while the asset interest margin have a positive significant impact on firm value. The GDP and inflation both have a positive significant relationship with firm value. The liquidity risk (loan to deposit ratio and liquid asset ratio) have a significant negative impact on return on equity of Nigerian banks. The GDP growth rate have a positive significant effect on the value of firm. Hence, this empirical study emphasizes and contributes to the dynamic role of liquidity risk and interest-rate risk and it’s implication on profitability and firm value of banks in Nigeria and suggest that further study can explore a comparative study between Nigeria and financial firms in developed economy.